(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This review paper examines the role of biological science in social protection, specifically in the enhancement of vulnerable people’ health and wellbeing. The paper highlights the significant contributions of biological science in disease prevention and control, nutritional interventions, environmental health, and biotechnology solutions for food security. The review provides specific examples of how advances in biological science have led to the development of vaccines, treatments, and diagnostic tools for infectious diseases, fortified foods and supplements for malnutrition, interventions to reduce exposure to environmental hazards, and crops and livestock that are more resistant to pests and diseases. The paper concludes that biological science plays a critical role in social protection, and its continued development and application will be essential for addressing the complex health and nutrition challenges faced by vulnerable populations.